Gambaran Perkembaangan Sosial Emosional Anak dan Implikasinya Terhadap Layanan Bimbingan Kelompok di TK ADE IRMA SURYANI I Kecamatan Pantai Cermin - Husnul Fatimah; Purbatua Manurung (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Research to determine the description of children's social emotional development and its implications for group guidance services at Ade Irma Suryani I Kindergarten, Pantai Cermin District, as well as the methods applied in this research, namely qualitative research and a field study approach. The method used for data collection was observation, interviews and documentation. The subjects in this research were the principal, teacher, and 2 young children at the Ade Irma Suryani I Pantai Cermin Kindergarten.The results of this research show that the description of children's social emotional development and its implications for group guidance services implemented in schools greatly influences the process of forming social emotional development in early childhood. The implementation of group guidance in this school is focused on group guidance methods and materials. The group guidance method used is by using the group guidance method. Meanwhile, group guidance materials use loose parts materials. Supporting and inhibiting factors for early childhood social emotional development depend greatly on the environment and the role of parents. The implications of group guidance in shaping the social emotional development process of early childhood show changes, where children can achieve self-understanding and relate to other people, take responsibility for themselves, and can demonstrate good social behavior.